Microbial Profiles and Antibiotic Resistance Patterns in Neonatal Sepsis: A Frequency Analysis: Microbial Profiles and Antibiotic Resistance Patterns in Neonatal Sepsis - Qaisar, Imran; Ahmed, Ishfaq; Hussain, Arif; Ullah, Irfan; Rafique, Aummara; Sheikh, Saba Afzal (Pakistan Journal of Health Sciences, 2026)
Neonatal sepsis remains an important cause of neonatal morbidity, mortality, and prolonged hospitalization, and the spectrum of causative organisms and their antibiotic susceptibility varies across settings. Updated local microbiological data are therefore essential for appropriate empirical therapy and antimicrobial stewardship. Objective: To determine the frequency of different microorganisms and their antibiotic susceptibility pattern in neonatal sepsis. Methods: This descriptive cross-sectional study was conducted in the Pediatric Ward of Bahawal Victoria Hospital, Bahawalpur, from 09-02-2024 to 08-08-2024. A total of 119 term neonates with clinical features of sepsis were included. Blood cultures were processed by standard microbiological methods, and antibiotic susceptibility was assessed against commonly used antibiotics. Data were analyzed using SPSS version 25.0. Post-stratification Chi-square test was applied, and p≤0.05 was considered statistically significant. Results: Escherichia coli was the most frequent isolate, identified in 41 (34.45%) cases, followed by Staphylococcus aureus in 24 (20.17%) and Klebsiella species in 19 (15.97%). Overall, gram-negative organisms predominated. Amikacin showed the highest sensitivity, 111 (93.28%), followed by gentamicin, 107 (89.92%), whereas relatively lower sensitivity was observed for ceftazidime, 85 (71.43%), cefotaxime, 86 (72.27%), and tobramycin, 91 (76.47%). Stratification by age and gender showed no statistically significant differences in microorganism distribution or antibiotic susceptibility (all p>0.05). Conclusions: Escherichia coli was the leading pathogen in neonatal sepsis in this cohort. The comparatively higher sensitivity to amikacin and gentamicin, together with lower sensitivity to some cephalosporins and tobramycin, supports the need for hospital-specific empirical antibiotic policies, regular antibiogram updates, and antimicrobial stewardship.